Investigation on torsional behaviour of CFRP strengthened square hollow steel section / Newsha Abdollahi Chahkand - Newsha , Abdollahi Chahkand (2013)
Fiber Reinforced Polymer (FRP) is one of the most popular methods for structural repairing and strengthening due to several properties such as non-corroding, higher strength, lighter weight, fatigue resistant, high modulus of elasticity, and low density. Extensive studies have been carried out on strengthening of steel members in flexural, shear, buckling, tensile, enhancing fatigue life and enhancing stability of steel members with FRP. It was found that there was no published literature concerning the investigation of torsional behavior of steel structures strengthened with FRP. This study examines the performance of Carbon Fiber Reinforced Polymer (CFRP) strengthened square hollow section (SHS) to withstand torsional moment using novel wrapping configurations of fiber reinforced polymer. Fifteen beam specimens were tested in order to investigate the effects of different number of layers and CFRP orientations on the performance of strengthened SHS under pure torsion. To investigate the effect of width to thickness ratio of SHS, two sets of specimens with different thickness were considered. In addition, theoretical predictions of ultimate torsional capacity of strengthened square hollow steel section beams were proposed based on classical torsion theory with modified geometric properties of the strengthened specimens. The best strengthening scheme was obtained for the specimen with four layers of alternating spiral (-45º) and reverse-spiral (45º) arrangement of CFRP with respect to the longitudinal axis of the specimen. The experimental results showed that CFRP strengthening of torsional member was more effective on a beam with larger width to thickness ratio. In general, it was observed that the failure mode of specimens strengthened with spiral direction fiber orientation was splitting, while the failure mode of reverse-spiral direction was rupture and debonding. By comparing the experimental results and the calculated values using the simplified expression, it was found that the values were in good agreement.